Indigenous Visions: Petrarch's Triumphs in 16th century Mexico - Mancosu, Paola (2016)
Murals of the Casa del Deán, inspired by Petrarch’s Triumphs and realized by indigenous painters in the late 16th century in the town of Puebla, provide a clear example of how image is used, effectively, in the process of adoption and “transgression” of the european canons in America. Triumphs and the Canzoniere were very widespread in the colonial America library market. However, if on one hand the Petrarchan canon acquires a relevant role in the Colonial mimesis processes, on the other hand is converted in a descolonizing space, where indigenous points of view coexist with Neoplatonic Renaissance style elements. Only through those gaps created by image within the Western codes is concretized – as Lezama Lima said – an “art of the contraconquista”.